Educational Significance of Father–Child Play Interactions: Implications for Early Cognitive and Socioemotional Development - bangsawan, Indra; Husin; Siti Mariah Ulfah (International Journal of Education and Teaching Zone, 2025)
This study investigates fathers’ unique contributions to the cognitive and emotional development of young children a dimension of early childhood education often overshadowed by maternal-focused research. It examines the evolving role of fathers from traditional authority figures to responsive play partners, the adaptive interaction strategies they employ, and the developmental outcomes of their engagement. Using a qualitative exploratory case study design, data were collected from 12 purposively selected fathers in Teluk Rendah Pasar Village, Tebo Regency, through in-depth interviews, participant observation, and documentation. Thematic analysis validated through source triangulation (fathers, mothers, and children) revealed three major findings. First, fathers experienced a meaningful transformation toward emotionally engaged and pedagogically responsive caregivers. Second, they developed adaptive strategies emphasizing intentional quality time, play integration into daily routines, and symbolic family rituals such as “Saturday morning adventures.” Third, paternal play fostered children’s cognitive growth (problem-solving, focus) and socioemotional competence (self-regulation, confidence, and social skills). These findings highlight the educational significance of paternal play as a catalyst for holistic child development and call for father-education initiatives and family-friendly workplace policies that support sustained paternal engagement in early learning.